ANALYSIS OF THE INFLUENCE OF SMART LEARNING IMPLEMENTATION ON IMPROVING THE QUALITY OF EDUCATION WITH THE TECHNOLOGY ACCEPTANCE MODEL APPROACH ON THE SEVIMA PLATFORM AT STIT PRINGSEWU - Evi Gusliana; Junaina Junaina (Institut Bakti Nusantara, 2026)
This study examines the effect of Smart Learning implementation on improving educational quality using the Technology Acceptance Model (TAM) approach on the SEVIMA platform at STIT Pringsewu. A quantitative method with a survey design was employed, involving 48 respondents consisting of 42 students and 6 lecturers. Data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) to evaluate relationships between perceived ease of use, perceived usefulness, behavioral intention, actual system use, and educational quality. The results indicate that perceived ease of use significantly influences perceived usefulness and behavioral intention. Furthermore, perceived usefulness has a positive effect on behavioral intention, which strongly affects actual system use. Actual system use significantly contributes to the improvement of educational quality. The model demonstrates strong explanatory power with an R-square value of 0.75 for educational quality. These findings confirm that Smart Learning implementation through the SEVIMA platform enhances learning effectiveness, academic interaction, and access to educational resources. This study contributes to the development of TAM in Islamic higher education contexts and provides practical implications for digital learning transformation strategies.